2017
DOI: 10.1021/acs.jpcb.6b11395
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effect of Carboxyl-Functionalized Task-Specific Ionic Liquids on UO22+ Removal: Experimental Study with DFT Validation

Abstract: Experimental study with DFT validation on the effect of radiation on 1-carboxymethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide ([HOOCCHMIM][NTf]) as a solvent and extractant in rapid homogeneous extraction of UO was performed for the first time. The radiolytic products of the anions and cations of [HOOCCHMIM][NTf] were identified by F NMR and high-resolution ESI-MS, respectively, and they were attributed to a decrease in UO partitioning. Experimental study with DFT validation for complexing reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It was found that the imide anions are relatively stable due to N–N σ 2 σ* 1 bond formation involving the parent anion, although a small amount of free radical CF 3 · and TfN· – is produced after radiation. In contrast, the cation 1,3-dialkyl imidazolium is not as so stable as the imide anions, and its radiation stability has been widely studied. The γ radiolysis of imidazolium ILs most likely leads to the formation of 2-imidazolyl radicals, which either are protonated or react with the parent cation forming C(2)–C(2) σσ*-bound dimer radicals. The elimination of substituted alkyl groups at the N­(1,3) sites was also observed for radiation effects. In addition, Adhikari et al , demonstrated that the introduction of a hydroxyl group into the alkyl side chain of the imidazolium moiety can result in a significant change in the physicochemical properties of ILs and promote various degradation channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the imide anions are relatively stable due to N–N σ 2 σ* 1 bond formation involving the parent anion, although a small amount of free radical CF 3 · and TfN· – is produced after radiation. In contrast, the cation 1,3-dialkyl imidazolium is not as so stable as the imide anions, and its radiation stability has been widely studied. The γ radiolysis of imidazolium ILs most likely leads to the formation of 2-imidazolyl radicals, which either are protonated or react with the parent cation forming C(2)–C(2) σσ*-bound dimer radicals. The elimination of substituted alkyl groups at the N­(1,3) sites was also observed for radiation effects. In addition, Adhikari et al , demonstrated that the introduction of a hydroxyl group into the alkyl side chain of the imidazolium moiety can result in a significant change in the physicochemical properties of ILs and promote various degradation channels.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the cation 1,3-dialkyl imidazolium is not as so stable as the imide anions, and its radiation stability has been widely studied. The γ radiolysis of imidazolium ILs most likely leads to the formation of 2-imidazolyl radicals, which either are protonated or react with the parent cation forming C(2)–C(2) σσ*-bound dimer radicals. The elimination of substituted alkyl groups at the N­(1,3) sites was also observed for radiation effects. In addition, Adhikari et al , demonstrated that the introduction of a hydroxyl group into the alkyl side chain of the imidazolium moiety can result in a significant change in the physicochemical properties of ILs and promote various degradation channels. The radiation stability of 1-(2-hydroxyethyl)-3-methylimidazolium was suggested to be lower than that of 1-ethyl-3-methylimidazolium. , However, the specific reactions and products of hydroxyl-functionalized imidazolium induced by radiation are still unclear.…”
Section: Introductionmentioning
confidence: 99%